2008
DOI: 10.1101/lm.921708
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of stress-induced prefrontal cortical impairment: Implications for mental illness

Abstract: The symptoms of mental illness often involve weakened regulation of thought, emotion, and behavior by the prefrontal cortex. Exposure to stress exacerbates symptoms of mental illness and causes marked prefrontal cortical dysfunction. Studies in animals have revealed the intracellular signaling pathways activated by stress exposure that induce profound prefrontal cortical impairment: Excessive dopamine stimulation of D1 receptors impairs prefrontal function via cAMP intracellular signaling, leading to disconnec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(108 citation statements)
references
References 256 publications
(232 reference statements)
2
106
0
Order By: Relevance
“…Chronic stress can be induced in the laboratory by continuously submitting animals to stressful situations, such as physical immobilization, and observing the effects on brain and/or behavior. For instance, several studies have used this approach to evaluate morphological changes caused by chronic stress on pyramidal neurons of the hippocampus, amygdala and prefrontal cortex [10,17,[62][63][64]. Other studies have shown effects on neurogenesis, synaptogenesis and myelination, as well as the availability of neurotransmitters and neurotrophic factors [65,66].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic stress can be induced in the laboratory by continuously submitting animals to stressful situations, such as physical immobilization, and observing the effects on brain and/or behavior. For instance, several studies have used this approach to evaluate morphological changes caused by chronic stress on pyramidal neurons of the hippocampus, amygdala and prefrontal cortex [10,17,[62][63][64]. Other studies have shown effects on neurogenesis, synaptogenesis and myelination, as well as the availability of neurotransmitters and neurotrophic factors [65,66].…”
Section: Discussionmentioning
confidence: 99%
“…Different acute stressors increase the release of dopamine and acetylcholine in the PFC (Thierry et al 1976;Abercrombie et al 1989;Mark et al 1996;Del Arco et al 2007). These neurotransmitters play a role in modulating working memory and attention (Sarter and Bruno 1997;Williams and Castner 2006), which have been suggested to be relevant to cope with stress (Sarter and Bruno 1997;Hains and Arnsten 2008). Animals reared in EC show a reduced response to acute handling (a mild stress challenge) of the dopaminergic but not the cholinergic systems in the PFC (Del .…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies have supported the human ones by showing, for example, that monkeys given cocaine swiftly develop prefrontal impairments 4 . And other researchers have found that stress, which frequently triggers drug use and relapse in people with addiction, seems to do so at least in part by shutting down prefrontal functions 5 . "We're really starting to understand the molecular basis of why this cortex falls apart with drugs of abuse, and during stress, and how those two interact, " says Amy Arnsten at Yale University School of Medicine in New Haven, Connecticut.…”
Section: Rethinking Rehabmentioning
confidence: 99%